Marketing Strategy Planning With SWOT Analysis and Quantitative Strategic Planning Matrix (QSPM) at CV. Dex Media Kreasi - Dimyati, Arjun Dwi Patlan; Wahyudin; Hamdani (Jurnal Sistem Teknik Industri, 2022)
The current condition of industrial competition is getting tougher, including in the printing industry. CV. Dex Media Kreasi is a printing company in Karawang. With this competition, CV. Dex Media Kreasi must have a strategy to survive and excel in attracting consumers. This study aims to analyze the best marketing strategy that can be applied by CV. Dex Media Kreasi. The method used is SWOT analysis and QSPM matrix. Based on the results of the SWOT analysis, the IFE value was 2,735 and the EFE was 2,784. Then obtained 12 alternative strategies were obtained from the SWOT matrix which was analyzed using QSPM to obtain priority strategies. Three priority strategies were obtained, namely ST2 Strategy with a TAS value of 5,424. WO3 strategy with a TAS value of 5,373. SO1 strategy with a TAS value of 5,354. The three proposed alternative strategies are Promoting with the help of influencers to increase consumer confidence, Rearranging the process and layout of production machines and regulating the availability of raw materials so that production delays do not occur, as well as establishing cooperation and conducting special promotions to large companies at least is in Karawang Regency.